2012 IEEE International Conference on Fuzzy Systems 2012
DOI: 10.1109/fuzz-ieee.2012.6250785
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall prediction in the northeast region of Thailand using Modular Fuzzy Inference System

Abstract: Abstract-In water management systems, accurate rainfall forecasting is indispensable for operation and management of reservoir, and flooding prevention because it can provide an extension of lead-time of the flow forecasting. In general, time series prediction has been widely applied to predict rainfall data. The conventional time series prediction models or artificial neural networks can be used to perform this task. However, such models are difficult to interpret by human analyst. From a hydrologist's point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…This study proposes a use of modular technique to perform monthly rainfall time series prediction. This study could be seen as an improvement of the work reported in [2]. …”
Section: Soft Computing Technique In Hydrological Time Series Presupporting
confidence: 59%
See 4 more Smart Citations
“…This study proposes a use of modular technique to perform monthly rainfall time series prediction. This study could be seen as an improvement of the work reported in [2]. …”
Section: Soft Computing Technique In Hydrological Time Series Presupporting
confidence: 59%
“…To evaluate the prediction accuracy, the proposed model was compared to hydrological common-used prediction models, namely, Autoregressive Moving Average (ARMA), Artificial Neural Network (ANN) [2], [3], [4], [5] as well as Fuzzy Inference System (FIS) [19], [20]. Furthermore, the proposed model is also compared to the model without aggregation method [2].…”
Section: Experimental Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations